2011
DOI: 10.1182/blood-2011-02-338517
|View full text |Cite
|
Sign up to set email alerts
|

Clonal drift demonstrates unexpected dynamics of the T-cell repertoire in T-large granular lymphocyte leukemia

Abstract: T-cell large granular lymphocyte leukemia (T-LGLL) is characterized by chronic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 45 publications
2
70
0
1
Order By: Relevance
“…By flow cytometry, in nearly 50% of the patients with T-LGLL studied, Clemente et al reported the phenomenon recognized as clonal drift in the Vb usage. 18 These authors observed that the clone size was smaller in the clonal drift group with respect to stable patients, supporting the concept that we are dealing with an early manifestation of the disease. CDR3 AA sequence was also shown to remain unaltered in stable clones, whereas expansions with different Vb restriction presented markedly different CDR3 sequences, suggesting that clonal drift was not associated with a conserved TCRg homology.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…By flow cytometry, in nearly 50% of the patients with T-LGLL studied, Clemente et al reported the phenomenon recognized as clonal drift in the Vb usage. 18 These authors observed that the clone size was smaller in the clonal drift group with respect to stable patients, supporting the concept that we are dealing with an early manifestation of the disease. CDR3 AA sequence was also shown to remain unaltered in stable clones, whereas expansions with different Vb restriction presented markedly different CDR3 sequences, suggesting that clonal drift was not associated with a conserved TCRg homology.…”
Section: Discussionmentioning
confidence: 53%
“…a change in the dominant T-cell clone observed in nearly 50% of LGLL patients, has been interpreted in line with this hypothesis. 18 Similarly, in both disorders, in vivo activation of STAT3 and the presence of somatic STAT3 mutations have been observed. [19][20][21][22] The observation that STAT3 SH2 somatic mutations can be found with a similar frequency in NK-cell and in T-cell disorders further indicates that a common mechanism is responsible for their pathogenesis, possibly driven by a shared genetic lesion irrespective of the cell lineage.…”
Section: Introductionmentioning
confidence: 92%
“…The presence of several STAT3 mutations could also be related to the clonal drift phenomenon, where the immunodominant LGL clone changes. 28 In addition, STAT3-mutated clones may carry somatic mutations in other genes, which affect the proliferative capacity of affected lymphocytes. These mutations could also drive the lymphoproliferation in patients without STAT3 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…It was established earlier that the major clones in CD8 + T-LGL leukemia patients are rarely identical, but the immunodominant clones are sometimes seen at a low frequency in other patients when the whole TCRB repertoire is analyzed. 28,[34][35][36] It should, however, be noted that the specific antigen can be recognized by a large number of different TCR types depending on the peptide presented, and the variation of HLA genes also affects antigen recognition. 37,38 The presence of a shared antigen driving the LGL proliferation has not, therefore, been ruled out, although our current understanding suggests more private antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Taking together, these results indicate that genomic mutations might only marginally account for in vivo activation of STAT3 in patients with LGLL and further emphasize the heterogeneity of mechanisms sustaining LGLL, highlighting the plasticity of proliferating cells. 43 …”
mentioning
confidence: 99%